Cholesterol can modulate mitochondrial aquaporin-8 expression in human hepatic cells - Danielli, Mauro (2017)
Hepatocyte mitochondrial aquaporin-8 (mtAQP8) works as a multifunctional membrane channel protein that facilitates the uptake of ammonia for its detoxification to urea as well as the mitochondrial release of hydrogen peroxide. Since early oligonucleotide microarray studies in liver of cholesterol-fed mice showed an AQP8 downregulation, we tested whether alterations of cholesterol content per se modulate mtAQP8 expression in human hepatocyte-derived Huh-7 cells. Cholesterol loading with methyl-β-cyclodextrin (mβCD):cholesterol complexes downregulated the proteolytic activation of cholesterol-responsive sterol regulatory element-binding protein (SREBP) transcriptions factors 1 and 2, and the expression of the target gene 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR). Under such conditions, mtAQP8 mRNA and protein expressions were significantly reduced. In contrast, cholesterol depletion using mβCD alone increased SREBP-1 and 2 activation and upregulated HMGCR and mtAQP8 mRNA and protein expressions. The results suggest that cholesterol can regulate transcriptionally human hepatocyte mtAQP8 expression likely via SREBPs. The functional implications of our findings are discussed. © 2017 IUBMB Life, 69(5):341–346, 2017.